2016
DOI: 10.3141/2573-20
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model for Estimating Temporal and Spatial Freeway Work Zone Delay Using Probe-Vehicle Data

Abstract: Highway lane closures due to road reconstruction and the resulting work zones have been a major source of nonrecurring congestion on freeways. It is extremely important to calculate the safety and cost impacts of work zones: the use of new technologies that track drivers and vehicles make that possible. A multilayer feed-forward artificial neural network (ANN) model is developed in this paper to estimate work zone delay by using the probe-vehicle data. The probe data include the travel speeds under normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The root mean square error (RMSE) is employed for performance evaluation. Comparing with a previous ANN model [7], we found that the developed model here with the work zone capacities suggested by HCM [33] and SVM has demonstrated itself as a sound model which improved prediction accuracy in terms of reduced RMSE. The results also suggest that the proposed hybrid machine-learning model with SVM outperforms the others for all three real-world study cases with greater prediction accuracy, especially when work zones are placed in daytime facing high traffic volumes.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The root mean square error (RMSE) is employed for performance evaluation. Comparing with a previous ANN model [7], we found that the developed model here with the work zone capacities suggested by HCM [33] and SVM has demonstrated itself as a sound model which improved prediction accuracy in terms of reduced RMSE. The results also suggest that the proposed hybrid machine-learning model with SVM outperforms the others for all three real-world study cases with greater prediction accuracy, especially when work zones are placed in daytime facing high traffic volumes.…”
Section: Discussionmentioning
confidence: 61%
“…Du and Chien [6] formulated the work zone delay considering time-varying traffic pattern, work zone capacity adjustment factors (e.g., light condition, heavy-vehicle percentage, and lane width), and shoulder usage. Deterministic queuing models are suitable for predicting delay for planning purposes but sometimes they have a limited ability to provide accurate prediction (i.e., delays), especially under significantly fluctuated traffic condition over time [7,8]. Further, the applied work zone capacity was either given or based on some simplified empirical equations, which also degrade the accuracy of prediction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations